2014
DOI: 10.1002/marc.201400533
|View full text |Cite
|
Sign up to set email alerts
|

Star-Pseudopolyrotaxane Organized in Nanoplatelets for Poly(ε-caprolactone)-Based Nanofibrous Scaffolds with Enhanced Surface Reactivity

Abstract: Herein, it is demonstrated that star pseudopolyrotaxanes (star-pPRs) obtained from the inclusion complexation of α-cyclodextrin (CD) and four-branched star poly(ε-caprolactone) (star-PCL) organize into nanoplatelets in dimethyl sulfoxide at 35 °C. This peculiar property, not observed for linear pseudopolyrotaxanes, allows the processing of star-pPRs while preserving their supramolecular assembly. Thus, original PCL:star-pPR core:shell nanofibers are elaborated by coaxial electrospinning. The star-pPR shell ens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…This is typically accomplished by a variety of post-modification reactions on hydroxyl groups, facilitating intermolecular interactions, such as ionic interactions [100,101] and click chemistries [102], potentially resulting in the immobilization of bioactive molecules. Although our studies did not focus on further development of the functionalized PCL, Elisseeff [103] and Schlatter [104,105] have reported various bioactive molecule immobilization on PCL-α-CD-IC nanofibers.…”
Section: Cyclodextrin Functionalized Aliphatic Polyester Nanofibersmentioning
confidence: 99%
See 3 more Smart Citations
“…This is typically accomplished by a variety of post-modification reactions on hydroxyl groups, facilitating intermolecular interactions, such as ionic interactions [100,101] and click chemistries [102], potentially resulting in the immobilization of bioactive molecules. Although our studies did not focus on further development of the functionalized PCL, Elisseeff [103] and Schlatter [104,105] have reported various bioactive molecule immobilization on PCL-α-CD-IC nanofibers.…”
Section: Cyclodextrin Functionalized Aliphatic Polyester Nanofibersmentioning
confidence: 99%
“…We overcame this difficulty by electrospinning pseudorotaxanes (PpR) from CFM and improved solution conductivity with the addition of BTEAC salt. Another easier method was reported by Schlatter’s research group, who reported on the fabrication of core–shell nanofibers comprised of four branched star-PpR or mikto-arm PpR for shell and neat PCL for core regions, respectively [104,105]. Small angle neutron scattering measurements (SANS) showed temperature-dependent shell stability/core instability of PpR in DMSO, based on which stable PpR solution was prepared for electrospinning (35 °C) (Figure 10A).…”
Section: Cyclodextrin Functionalized Aliphatic Polyester Nanofibersmentioning
confidence: 99%
See 2 more Smart Citations
“…The polypseudorotaxanes adopted a nanoplatelet arrangement, which was maintained after electrospinning. The core-shell structure ensured that the hydroxyl groups of αCD were available on the fibers surface for subsequent immobilization of active substances [ 103 ].…”
Section: Electrospun Mats Of Mixtures Of Cyclodextrins and Polymermentioning
confidence: 99%